The genus Stactobia McLachlan (Trichoptera, Hydroptilidae) in Japan - Ito, Tomiko (Zootaxa, 2017)
The caddisfly genus Stactobia McLachlan (Hydroptilidae) is revised for Japan. Males are redescribed for 6 known species, Stactobia japonica Iwata, S. makartschenkoi Botosaneanu & Levanidova, S. inexpectata Botosaneanu & Nozaki, S. hattorii Botosaneanu & Nozaki, S. nishimotoi Botosaneanu & Nozaki, and S. distinguenda Botosaneanu & Nozaki. Six new species are described, also based on males: S. kanagawa, S. gunma, S. chichibu, S. yona, S. urauchi, and S. campire. A Taiwanese species, S. semele Malicky & Chantaramongkol, is recorded from Japan for the first time. Final instar larvae and their cases of 8 species and early instar larvae of 2 species are also described.